2005
DOI: 10.1002/mats.200500028
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Kinetic Model for Thermal Crosslinking of Rubbery Polymers

Abstract: Summary: A kinetic model for the thermal crosslinking of rubbery polymers is presented. The reaction mechanism used to develop the model includes thermal radical generation producing a polymeric radical and a primary radical, crosslinking from attack of a polymer radical to any inactive polymer molecule, bimolecular radical termination among chains of any degree of branching, and radical termination between a polymer radical and a primary radical from the thermal radical generation. The overall polymer populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Based on the above mechanism and kinetic rate information, a model can be constructed through which quantitative relationships between the product properties and the reaction conditions are established. In general, there are two approaches to modeling the complex reaction network for macromolecules, namely, the numerical population balance and the kinetic stochastic method. ,,, Under a proper scheme of parameterization, both strategies are capable of calculating properties, such as molecular weight distribution (MWD) and gel content that closely match with experimental data. However, the implementation of the stochastic method does not require closure rules and the mono-radical approximation (that are commonly used in the population balance method ,, ), and is therefore numerically easier to be adopted in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above mechanism and kinetic rate information, a model can be constructed through which quantitative relationships between the product properties and the reaction conditions are established. In general, there are two approaches to modeling the complex reaction network for macromolecules, namely, the numerical population balance and the kinetic stochastic method. ,,, Under a proper scheme of parameterization, both strategies are capable of calculating properties, such as molecular weight distribution (MWD) and gel content that closely match with experimental data. However, the implementation of the stochastic method does not require closure rules and the mono-radical approximation (that are commonly used in the population balance method ,, ), and is therefore numerically easier to be adopted in this work.…”
Section: Resultsmentioning
confidence: 99%
“…A kinetic model incorporating many of the features discussed here has been implemented by Vivaldo -Lima et al and used to fi t experimental data with good success, as shown in Figure 3.1 [36] .…”
Section: Overall Kineticsmentioning
confidence: 99%
“…The NFT, either in its original form or in improved versions, has been used to model the emulsion polymerization of vinyl monomers with chain transfer to polymer (CTP) and termination by combination (TC), [26] and the copolymerization of vinyl/ divinyl monomers. [27][28][29] Vivaldo-Lima et al [30] developed a kinetic model to calculate the branching and crosslinking fractions, as well as number-and weight-average molecular weights in the thermal crosslinking of rubbery polymers. In the development of their model, Vivaldo-Lima et al [30] used some of the ideas of the NFT.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Vivaldo-Lima et al [30] developed a kinetic model to calculate the branching and crosslinking fractions, as well as number-and weight-average molecular weights in the thermal crosslinking of rubbery polymers. In the development of their model, Vivaldo-Lima et al [30] used some of the ideas of the NFT. The group of Morbidelli has also been active in the study of gelation, particularly in water-dispersion polymerization processes.…”
Section: Introductionmentioning
confidence: 99%